Restoration of Coastal Dunes - Martínez, Luisa M.; Gallego-Fernández, Juan B.; Hesp, Patrick A. (Springer Series on Environmental Management, 2013)
The continuously growing human population along the world's coasts will exacerbate the impact of human activities on all coastal environments. Restoration activities will therefore become increasingly important. In particular, sandy shores and coastal dunes will require significant restoration efforts because they are preferred sites for human settlement, industrial and urban development and tourism. With this book experts in the field present a comprehensive review of restoration studies and activities, where 'successful' and 'failed' studies or approaches from around the world are contrasted and compared. A major asset the book provides is a compendium of studies showing that coastal dune restoration has many definitions and thus leads to many different actions. This volume addresses those with an interest in conservation ecology and biology, coastal dune dynamics and geomorphology, and coastal management who are seeking information on the different strategies for coastal dune restoration applied in different regions of the world. Finally, it will be a valuable resource for coastal scientists and planners, as well as for local and state officials, residents of coastal communities, environmental advocates and developers.